The concept of interactive in video installation artworks: The manipulation of space - Zhao, Ming; Musnin Misdih; Baharuddin Mohd Arus (Akademi Seni dan Teknologi Kreatif, 2021)
In traditional works of art, artists mainly show two-dimensional and three-dimensional spatial concepts to express their artistic concepts, lacking interaction with the audience. After the concept of interaction brought by video installation art, These things have completely changed, and more and more art works are interactive. With the introduction of video and computer related technology, video works expand the traditional concept of space. It makes artists realize new creative ideas and styles. In addition, these new media have created a new concept of space, which makes the actual dimension of exhibition space a necessary element of art creation, rather than a passive display place of art works. Therefore, this paper determines the concept of interaction and how artists manipulate space through the works of video installation art. In addition, through the analysis of the samples of video installation works, the critical theory of Edmund Burke Feldman (1980) is used to prove that the video installation works of art have the concept of interaction. This study adopts qualitative research methods. Under the background of contemporary art, focusing on the concept of interaction, combined with visual analysis of works of art, this study collects data from literature for analysis. The result of this study is to deeply explore the video installation art works as the media of artists, and make the audience closer to the creator through the concept of interaction.